A Brief History of Fruit - Andrews, Kimberly Quiogue, 1983- (Book collections on Project MUSE., 2020)
"In Kimberly Quiogue Andrews's award-winning full-length debut, A Brief History of Fruit, we are shuttled between the United States and the Philippines in the search for a sense of geographical and racial belonging. Driven by a restless need to interrogate the familial, environmental, and political forces that shape the self, these poems are both sensual and cerebral: full of "the beautiful science," as she puts it, of "naming: trees of one thing, then another, then yet another." Colonization, class dynamics, an abiding loneliness, and a place's titular fruit-tiny Filipino limes, the frozen berries of rural America-all serve as focal markers in a book that insists that we hold life's whole fragrant pollination in our hands and look directly at it, bruises and all. Throughout, these searching, fiercely intelligent and formally virtuosic poems offer us a vital new perspective on biracial identity and the meaning of home, one that asks us again and again: "what does it mean, really, to live in a country?""--